Formulation development and evaluation of site specific periodontal fibers of metronidazole and minocycline hcl (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Periodontal disease is a collective term for a variety of pathological conditions characterized by relapse and inflammation of the gums, periodontal sinews, alveolar bone, and dental cementum. It is a confined inflammatory reaction caused by bacterial infection of a periodontal pocket in conjunction with subgingival plaque. Even though bacteria are the primary cause of periodontal disease, the presence of microbial pathogenic aspects may not be required to cause periodontitis. Periodontal pathogens produce harmful byproducts and enzymes that disrupt extracellular matrices as well as host cell membranes in order to produce nutrients for their growth. A number of antimicrobial products are summarized, as well as the composition of the delivery systems, their use, clinical results, and release. The goal of using an intrapocket device for antimicrobial agent delivery is to achieve and maintain therapeutic drug concentration for the desired period of time. With precise control of the rate at which a specific drug dosage is released from a delivery system without the need for frequent administration, novel controlled drug delivery systems are capable of improving patient compliance as well as therapeutic efficacy. Because of their low cost, greater stability, non-toxicity, biocompatibility, non-immunogenicity, and biodegradability, these are considered superior drug delivery systems. In this study, a site-specific periodontal drug delivery system for Metronidazole and Minocycline HCl was developed. The augmented fibre formulation G-II laterally with scaling and root planning was effective in eliminating local irritants, reducing gingival inflammation, reducing pocket depth, and increasing clinical addition. Method (A) revealed a determined drug release of 81.8 percent over a period of 120 hours, while method (B) released 84 percent drug(s) over a period of 264 hours. For the optimized formulation, the value of n is assumed to be 0.9314 and follows zero-order. It also measured the restricted infection and prevented the formation of new lesions. In the current revision, there was a significant decrease in mean plaque index, gingival index, sulcus bleeding index, and probing pocket depth, as well as a significant increase in clinical affection. The current study's local drug delivery system is artless and simple to use.